On the asymptotic behaviour of the spectral function estimation of a multivariate stationary Gaussian time series - Bentkus, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Бенткус. Об асимптотическом поведении оценки спектральной функции многомерной стационарной гауссовской последовательностиR. Bentkus. Apie daugiamatės stacionarios Gauso sekos spektrinės funkcijos įvertinimo asimptotiką